Pengaruh High Performance Work System Terhadap Kinerja Melalui Resiliensi pada Karyawan Bank: (The Effect of High Performance Work System on Performance through Resilience in Bank Employees) - Haidar Paramanandana; Anang Kistyanto (UPT Penerbitan Universitas Jember, 2021)
This article aims to study the effect of the High-Performance Work System (HPWS) on employee performance through employee resilience to employees of Bank BTN in Surabaya city. This study uses a type of causality research that uses a quantitative approach. The sampling technique used disproportionate stratified random sampling. Respondents are 57 employees of Bank BTN in Surabaya. The statistical analysis in this study used the Structural Equation Model (SEM) by using the SmartPLS 3.0 software for data processing assistance. The results show that HPWS had no effect on employee performance. HPWS has a positive and significant effect on employee resilience. Employee resilience has a positive and significant effect on employee performance, and HPWS has a positive and significant impact on employee performance through employee resilience.